If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 4) = 5x + 1 Reorder the terms: 2(4 + 3x) = 5x + 1 (4 * 2 + 3x * 2) = 5x + 1 (8 + 6x) = 5x + 1 Reorder the terms: 8 + 6x = 1 + 5x Solving 8 + 6x = 1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 8 + 6x + -5x = 1 + 5x + -5x Combine like terms: 6x + -5x = 1x 8 + 1x = 1 + 5x + -5x Combine like terms: 5x + -5x = 0 8 + 1x = 1 + 0 8 + 1x = 1 Add '-8' to each side of the equation. 8 + -8 + 1x = 1 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 1 + -8 1x = 1 + -8 Combine like terms: 1 + -8 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| a(x^2-3)-2(x^2-3)=0 | | 5+10x=2x-11 | | 5x(x+1)=5-2x | | 9x-89= | | -38-7x=2-7(x+6) | | x^3-2x^2+16x-60=0 | | 3x-8+4x+12=6x+15 | | 4x^2+8x+k=0 | | (2w+3u)(4w+3u-7)= | | 12z=21-8x | | 0.5+0.3y=0.7y-0.3. | | Log(4)(6-5x)=1 | | 3x+5=97-5x | | sqrt(6x+1+2)=7 | | -10=-3x-47 | | 5x^2-4x+2whenx=-2 | | 2ax^2-2a^2x+10x-10a=0forx | | x^4+2x^2-x+4=0 | | 48x+y=340 | | 2ax^2-2a^2x+10x-10a=0 | | 5r^4-3125= | | y^4+4y^2+5y=0 | | 2(3x+5)=32 | | x^4+4y^2+5y=0 | | 2.5f=40 | | 6-7(x-1)x=7 | | 20+x=3x | | -89=5x+4x+10 | | 10/10= | | 5+3x=10-2x | | x/3-x/4-1/6=7/3? | | 5t^2-7t-6=0 |